Studi Daya Dukung Lingkungan dan Tingkat Kekritisan Berdasarkan Pendekatan Ketersediaan Air Kota Balikpapan - Harfadli, Muhammad Ma'arij; Ulimaz, Mega (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
One of the priority problems in Balikpapan is the limited availability of raw water. This is due to the rapid growth of domestic and non-domestic activities in Balikpapan while the Manggar Reservoir as the main source of Â water supply is almost close to maximum capacity. The impact that will occur is a decrease in the environmental carrying capacity of Balikpapan. So it is necessary to predict when the availability of water in Balikpapan will reach a critical point. The method used in this study is to calculate the need and availability of water in Balikpapan, then calculate the ratio of water availability and demand to determine the carrying capacity and the water criticality index. The results of the calculation of the Environmental carrying capacity status in this study indicate that the water resources in Balikpapan from 2019 to 2029 are worth between 1-2 so that they are included in the conditional safe category. The calculation of the Water Critical Index Â shows that in 2019 and 2024 is approaching critical (50-70%). Meanwhile, in 2029 the water criticality index of Balikpapan will reach critical status (84%). So it is necessary to conserve water resources in Balikpapan.